Clinical and microbiological study of non-gonococcal urethritis with particular reference to non-chlamydial disease. Issue 5 (October 1981) - Munday, P E; Thomas, B J; Johnson, A P; Altman, D G; Robinson, D T
Abstract : A double-blind placebo-controlled study of minocycline in 221 men with non-gonococcal urethritis (NGU) was undertaken. Techniques were used which enabled diagnoses of chlamydial and mycoplasmal infections to be made within 24 hours of a patient attending a clinic. All patients from whom Chlamydia trachomatis was isolated were treated with minocycline, while patients from whom Ureaplasma urealyticum or Mycoplasma hominis was isolated, or from whom no micro-organisms were isolated, were treated on a double-blind basis with either minocycline or placebo. Chlamydia were isolated from 77 (35%) patients and were eradicated by minocycline from 76 (99%). Ureaplasmas were isolated initially from 96 (43%) patients. Treatment with minocycline eradicated them from 43 of 52 (83%) patients, and they disappeared from six of 31 (19%) patients who were treated with placebo. After one week significantly more patients had responded clinically to minocycline than to placebo. The response to minocycline was not influenced by the microbiological status of the patients, which suggests that ureaplasmas are playing a similar role to chlamydia in the pathogenesis of the disease and that an antibiotic-sensitive micro-organism may be producing disease in the isolate-negative group. An immunological approach is required to resolve the problem of the persistent urethral inflammation which occurred despite eradication of the micro-organisms.